Formation of a system of target indicators for rating and integral evaluation of the efficiency of the organization of the provision of medical care to patients with diabetes mellitus in the Russian Federation regions - I. A. Mikhailov; V. V. Omelyanovsky; M. V. Shestakova; N. G. Mokrysheva (Сахарный диабет)
AIM: Formation of a system of target indicators for rating and integral assessment of the effectiveness and efficiency of the organization of medical care for patients with diabetes mellitus in the Russian Federation regions.MATERIALS AND METHODS: The study was an expert survey in the form of a structured interview. At the first stage, we performed the primary selection of indicators. At the second stage, the selection of experts took place in accordance with the inclusion criteria, and the assessment of the level of expert competence was assessed based on a self-assessment survey. Further, criteria we formulated for expert evaluation of the significance of the selected indicators in accordance with the principles used in the development of national and federal projects. The indicators were divided into two groups: additional (process) and main (outcome). To quantify the degree of agreement between the experts’ answers, Kendall’s concordance coefficient (W) was calculated. The significance of differences was assessed using the nonparametric Friedman test.RESULTS: Only indicators with a high degree of agreement between experts and the presence of statistical significance in terms of the concordance coefficient are recommended as target indicators. The following main and additional indicators satisfy these requirements: mortality from cardiovascular complications of type 2 diabetes (people per 100,000 population); the proportion of patients with type 1 and 2 diabetes mellitus provided with medical devices out of the total number of patients with type 1 and 2 diabetes mellitus (percentage); the proportion of patients with type 1 and 2 diabetes mellitus with high amputations of all patients with type 1 and 2 diabetes mellitus with any amputations (percentage); and other indicators.CONCLUSION: We selected indicators that can be used both for the integral rating of the constituent entities of the Russian Federation, and in the formation of federal projects or departmental target programs. The results of the study can also be used to organize a system for monitoring the effectiveness of the implementation of these projects and programs.